Les espaces d’engagement d’un mouvement social face à un régime spatial patronal du travail : une géographie du conflit chez Delhaize en 2023 - Alexandre Orban (Belgeo)
This article proposes a geographical analysis of the 2023 labour conflict at Delhaize. On the one hand, the spaces of engagement are analyzed through the general spatial dynamics of the continuous strike in the shops from the 8th of March to the 10th of May 2023. We observe an inter-regional difference between Flanders and Wallonia, a high level of combativity in Brussels shops, more active intra-regional areas such as Hainaut and Liège, and the urban nature of these collective actions. The specific dynamics of abrupt peaks, Saturday mobilizations, employees strongholds and persistent last-stands are also highlighted. On the other hand, we analyzed the spatial regime of work in terms of its influence on the social movement opposing it. Three main means of influence and their spatialities are examined: the territories of intimidation of the legal actions, the intervention zones of repressive forces and the waves of franchising. The results show that, respectively, the former serve as a legal framework enabling the latter, which have the greatest impact, to be applied. As for the franchising waves, the data does not confirm any intention on the part of Delhaize's management to strategically exploit them.